Data driven extraction of challenging situation for autonomous vehicles - Krishna, Sagar (2019)
Autonomous vehicles or Self-Driven Vehicles (SDVs) are becoming increasingly common in Singapore and for a wide variety of applications – from first-and-last-mile commutes to logistics. The areas of deployment are similarly diverse, ranging from docks to housing estates and highways. This variance in operating environments necessitates careful validation and analysis of SDVs in contextual situations before deployment.